ANALISA TEKNO-EKONOMI PENGUJIAN TEGANGAN TINGGI PADA PLN UNIT PELAYANAN TRANSMISI CAWANG - Ihsan, Muhammad; Assagaf, Aminullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
High-Voltage (HV) Testing on the 150‑kV High-Voltage Underground Cable (SKTT) system is essential to verify insulation integrity following faults or relocations associated with National Strategic Projects. Conventional testing methods using a Mobile Test Unit (MTU) often face cost and logistical constraints. This study evaluates the effectiveness of a reverse energization method utilizing a 150/20‑kV Power Transformer as an alternative test source, using the 150‑kV SKTT Taman Rasuna–Durentiga Circuit #2 as the case study. ETAP simulations indicate that this method can deliver a 34.7‑A test current on the 150‑kV side through an injection of 260.4 A from the 20‑kV side at a test voltage of 152.8 kV. Operational safety is ensured through cascading protection coordination between the Line Current Differential relay (<100 ms) and the 20‑kV incoming OCR (100 ms). From an economic standpoint, the reverse‑transformer method requires only IDR 26.43 million, significantly lower than the MTU cost of IDR 358.51 million, resulting in 92.63% cost savings. The findings demonstrate that the reverse power‑transformer method is a reliable, safe, and highly cost‑efficient testing solution for PLN UPT Cawang operations.